2022
DOI: 10.7554/elife.78129
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for global ocean plankton biogeography shaped by large-scale current systems

Abstract: Biogeographical studies have traditionally focused on readily visible organisms, but recent technological advances are enabling analyses of the large-scale distribution of microscopic organisms, whose biogeographical patterns have long been debated. Here we assessed the global structure of plankton geography and its relation to the biological, chemical, and physical context of the ocean (the ‘seascape’) by analyzing metagenomes of plankton communities sampled across oceans during the Tara Oceans expedition, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 65 publications
5
54
2
3
Order By: Relevance
“…While the sampling route did not sample both basins the same year, there is a continuum in the seasons sampled. Both basins have a relatively high seasonality, yet recent studies ( 4, 8, 9 ) suggest that relatively stable plankton biogeographies exist at the global scale, which is confirmed here (see below). In terms of connectivity, values of minimum transport time by currents (Tmin) computed from previous studies ( 8, 9 ) between each proximal station (defined by this minimum transport time) confirm that the flow of currents is directed from the Atlantic into the Arctic (Figure 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…While the sampling route did not sample both basins the same year, there is a continuum in the seasons sampled. Both basins have a relatively high seasonality, yet recent studies ( 4, 8, 9 ) suggest that relatively stable plankton biogeographies exist at the global scale, which is confirmed here (see below). In terms of connectivity, values of minimum transport time by currents (Tmin) computed from previous studies ( 8, 9 ) between each proximal station (defined by this minimum transport time) confirm that the flow of currents is directed from the Atlantic into the Arctic (Figure 1).…”
Section: Resultssupporting
confidence: 83%
“…They are key players in many biogeochemical processes such as primary production via photosynthesis ( 1 ), carbon export to the deep ocean ( 24 ) and essentially sustain the entire oceanic trophic system ( 5 ). Many studies based either on satellite ( 6, 7 ) or genomic data ( 4, 8, 9 ) revealed a mainly latitudinal and temperature driven biogeographical partitioning of the oceans. While some species have strictly defined environmental niches ( 4, 10 ), some display cosmopolitan biogeographies, such as Bathycoccus prasinos which is present in both polar and temperate oceans ( 11 ) or Pelagomonas calceolata that is cosmopolitan in all except polar oceans ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oceans cover 70% of the surface of our planet and are home to myriad bacterial species that are responsible for many of Earth’s crucial biogeochemical functions ( 1, 2 ), including fixing carbon and nitrogen, recycling nutrients and dissolved organic matter, and degrading biomass. Surveys of the ocean microbiome over broad spatial and temporal scales have revealed repeatable patterns across seasons ( 36 ), latitude ( 7 ), and depth ( 8 ), which have been linked to a variety of environmental factors, including temperature ( 3, 4, 8, 9 ), water mixing ( 10, 11 ), nutrient availability ( 12 ), light ( 13 ), and the occurrence of phytoplankton blooms ( 6 ). Nevertheless, general principles underlying the compositional turnover of vital marine bacterial communities are lacking, impairing our ability to predict the response of ocean systems to future environmental changes.…”
Section: Main Textmentioning
confidence: 99%
“…Microbial eukaryotes have been widely explored in marine ecosystems (P. López-García et al 2001;Lovejoy, Massana, and Pedrós-Alió 2006;Worden, Cuvelier, and Bartlett 2006;Countway et al 2007;Massana and Pedrós-Alió 2008;Alexander et al 2009;Stoeck et al 2010;Logares et al 2014;Vargas et al 2015), whereas there are fewer studies available regarding their distribution and diversity in soils (Fell et al 2006;Shen et al 2014;Moon-van der Staay et al 2006;Mahé et al 2017) and in freshwater systems (Šlapeta, Moreira, and López-García 2005;Debroas et al 2017). Freshwater ecosystems are more fragmented and isolated (Dodson 1992;Reche et al 2005) in comparison to the open ocean where microbial communities are transported by currents on a global scale (Villarino et al 2018;Richter et al 2020). This intrinsic lower connectivity of freshwater ecosystems hinders the dispersal of freshwater organisms and increases the genetic diversity (Dias et al 2013).…”
Section: Introductionmentioning
confidence: 99%